Translating Workforce Development Policy Interventions for Community Health Workers: Application of a Policy Research Continuum. (March 2020) - Fulmer, Erika B.; Barbero, Colleen; Gilchrist, Siobhan; Shantharam, Sharada S.; Bhuiya, Aunima R.; Taylor, Lauren N.; Jones, Christopher D.
Abstract : Context: There is a need for knowledge translation to advance health equity in the prevention and control of cardiovascular disease and type 2 diabetes. One recommended strategy is engaging community health workers (CHWs) to have a central role in related interventions. Despite strong evidence of effectiveness for CHWs, there is limited information examining the impact of state CHW policy interventions. This article describes the application of a policy research continuum to enhance knowledge translation of CHW workforce development policy in the United States. Methods: During 2016-2019, a team of public health researchers and practitioners applied the policy research continuum, a multiphased systematic assessment approach that incorporates legal epidemiology to enhance knowledge translation of CHW workforce development policy interventions in the United States. The continuum consists of 5 discrete, yet interconnected, phases including early evidence assessments, policy surveillance, implementation studies, policy ratings, and impact studies. Results: Application of the first 3 phases of the continuum demonstrated (1) how CHW workforce development policy interventions are linked to strong evidence bases, (2) whether existing state CHW laws are evidence-informed, and (3) how different state approaches were implemented. Discussion: As a knowledge translation tool, the continuum enhances dissemination of timely, useful information to inform decision making and supports the effective implementation and scale-up of science-based policy interventions. When fully implemented, it assists public health practitioners in examining the utility of different policy intervention approaches, the effects of adaptation, and the linkages between policy interventions and more distal public health outcomes.